THEORY OF FORCES DYNAMICLY INFLUENCED ON QUARRY TRUCKS (Modern education and development, 2025)
The article presents a mathematical development that allows determining the optimal ratio of construction and operational parameters of dump trucks, ensuring the stability of its movement when passing through uneven, deep areas of highways. The theory and results of experimental studies on the damage of truck transmissions as a result of the influence of road defects on the movement of a dump truck on unsuitable quarry roads are presented.